Satirical Analysis of Political Commentary in Kaesang Pangarep’s Podcast - Mutiara Alda Lekson; Fila Alfia; Arella Chaterina Manalu; Afrahul Fadhillah Parinduri; Nico Sahpudan Simorangkir; Dian Marisha Putri (English Lecturers and Teachers Association (ELTA), 2025)
The rapid development of digital communication has transformed political discourse, with platforms like YouTube becoming significant arenas for satirical commentary. This study focuses on analyzing the use of satire in Kaesang Pangarep’s podcast episode Inilah Kelebihan Pelawak Kalau Masuk Politik, which garnered over 5.1 million views. The research investigates how satire is categorized based on Holbert’s framework and explores the political and social issues critiqued through satirical elements. Holbert’s framework classifies satire into three types: Horatian (light and humorous critique), Juvenalian (sharp and scathing criticism), and Menippean (broad, philosophical critique of societal attitudes). Employing qualitative content analysis, this study transcribes the podcast to identify and analyze satirical elements, focusing on both explicit statements and underlying cultural nuances. The findings indicate that Horatian satire humorously critiques political party-switching, Juvenalian satire sharply condemns political monetization, and Menippean satire examines societal attitudes toward celebrity involvement in politics. These satirical critiques serve three primary functions: exposing political opportunism, highlighting social inequalities, and engaging audiences through humor while fostering political awareness. The study concludes that satire in digital platforms like YouTube bridges entertainment and political critique, encouraging public reflection on socio-political issues in Indonesia. The high viewership of the podcast emphasizes the effectiveness of digital satire in engaging audiences and reshaping political discourse. Future research could explore the influence of such content on public perception and voter behavior, particularly in the evolving landscape of digital media. Keywords : Political commentary; Political discourse; Satirical language; Social hierarchies